STUDI HISTOKIMIA LEKTIN PADA SEL-SEL SPERMATOGENIK TESTIS MUNCAK (Muntiacus muntjak muntjak) (Lectin Histochemical Study of Testicular Spermatogenic Cells in Muntjak (Muntiacus muntjak muntjak)) - Wahyuni, Sri; Agungpriyono, Srihadi; Adnyane, I. Ketut Mudite; Hamny, Hamny; Jalaluddin, Muhammad; Gholib, Gholib; Akmal, Muslim; Adam, Mulyadi; Aliza, Dwinna; Siregar, Tongku Nizwan (Jurnal Kedokteran Hewan, 2016)
The objective of this study was to identify the type of specific glycoconjugates and its distribution in testicular spermatogenic cells in muntjak (Muntiacus muntjak muntjak) based on lectins histochemistry. An adult male muntjak aged 4-5 years old in hard antler period was used in this study. Testicular tissue was fixed in Bouin solution and processed histologically. Histochemistry method was performed using six types biotinylated lectins such as peanut agglutinin (PNA), soybean agglutinin (SBA), wheat germ agglutinin (WGA), ricinus communis agglutinin (RCA), concanavalin A (Con A), and ulex europaeus agglutinin I (UEA I) with 20 g/ml of concentration for PNA lectins and 15g/ml for other type of lectins. The results showed that glycoconjugates were detected by all type of lectins except UEA I in testicular spermatogenic cells with variation in distribution pattern and also the intensity of lectins binding. Glycoconjugates -galactose, -glucose, mannose, Nacetylgalactosamine, N-acetylglucosamine and sialic acid were stained intensely by lectins in golgy-cap phase and acrosomal phase of spermatids. Glycoconjugate N-acetylgalactosamine was the sugar residues which distributed abundantly that marked by positive reaction with PNA, SBA, and RCA lectins. In conclusion, glycoconjugates are detected in testicular spermatids cells of muntjak indicated that glycoconjugates have an important role in spermatogenesis particularly in spermiogenesis.Key words: glycoconjugates, lectins, spermatid, spermatozoa, muntjak